2023
DOI: 10.3390/ijms24065301
|View full text |Cite
|
Sign up to set email alerts
|

DHEA and Its Metabolites Reduce the Cytokines Involved in the Inflammatory Response and Fibrosis in Primary Biliary Cholangitis

Abstract: Dehydroepiandrosterone (DHEA) is an abundant steroid and precursor of sex hormones. During aging, the reduction in DHEA synthesis causes a significant depletion of estrogens and androgens in different organs, such as the ovaries, brain, and liver. Primary Biliary Cholangitis (PBC) is a cholestatic liver disease that begins with immune-mediated bile duct damage, and is followed by liver fibrosis, and finally, cirrhosis. PBC primarily affects postmenopausal women, with an average age of diagnosis of 65 years, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The in ammatory response and brosis associated with PBC can potentially be modulated by DHEA (dehydroepiandrosterone) and its metabolites. Previous works have shown that the sulfonated metabolite, DHEA-S, can reduce the levels of pro-in ammatory interleukins (IL-8 and TNF-α) in PBC-like cholangiocytes, as well as the pro-brotic interleukin IL-13 in hepatocytes (Blatkiewicz et al in 2023). Furthermore, DHEA has also been shown to have a protective function in hepatocytes against oxidative stress induced by tert-butylhydroquinone (tBHQ), as well as apoptosis in HEPG2 cells (Kilanczyk et al in 2022).…”
Section: As Reported Bymentioning
confidence: 99%
“…The in ammatory response and brosis associated with PBC can potentially be modulated by DHEA (dehydroepiandrosterone) and its metabolites. Previous works have shown that the sulfonated metabolite, DHEA-S, can reduce the levels of pro-in ammatory interleukins (IL-8 and TNF-α) in PBC-like cholangiocytes, as well as the pro-brotic interleukin IL-13 in hepatocytes (Blatkiewicz et al in 2023). Furthermore, DHEA has also been shown to have a protective function in hepatocytes against oxidative stress induced by tert-butylhydroquinone (tBHQ), as well as apoptosis in HEPG2 cells (Kilanczyk et al in 2022).…”
Section: As Reported Bymentioning
confidence: 99%
“…Kahnamoui et al found that respiratory sensitivity was associated with miRNA expression levels in mice of different sexes [ 8 ]; Rosenberg et al found an association between the effects of different sexes on smoking and lung development [ 9 ]. In addition, research showed that certain miRNAs are expressed differently in different sexes during fetal development [ 10 , 11 ], which, in turn, results in different developmental processes. There have even been studies of male–female gender differences in miRNA-associated methylation modifications during solid tumor pathology [ 12 ].…”
Section: Introductionmentioning
confidence: 99%